What drives people’s protective behaviors during the early stage of the COVID-19 pandemic in China - Pang, Zhenjing; Zhao, Ce; Xue, Lan (Frontiers in Psychology, 2022)
This study systematically examined people’s protective behaviors against COVID-19 in China, and particular attention was given to people’s perceived threat and information processing strategies. This study constructed a conceptual model and used structural equation modeling to explore this issue, a questionnaire survey was conducted to collect data involving 4605 participants during the early stage of COVID-19 pandemic outbreak in China. The results showed that people’s initial information acquisition played an important role in their behavioral responses, acquiring more initial information about COVID-19 would make them perceive a higher threat and present a higher demand for information, then making them more likely to seek and process information, and subsequently motivating their protective behaviors. In addition to increasing people’s information needs, perceived threat could also strengthen the analytical assessment and affect protective behavior positively, but failed to predict experiential assessment. Driven by information need, information seeking had a significantly positive influence on protective behavior, it also facilitated analytical assessment and decrease experiential assessment, thus predicting people’s protective behaviors. Protective behaviors were spurred by analytical assessment, but negatively influenced by experiential assessment. Theoretical contribution, practical implications and research limitations were also discussed.